Evaluation of Humoral Immunity to Mycobacterium tuberculosis-Specific Antigens for Correlation with Clinical Status and Effective Vaccine Development - Mamiko Niki; Maho Suzukawa; Shunsuke Akashi; Hideaki Nagai; Ken Ohta; Manabu Inoue; Makoto Niki; Yukihiro Kaneko; Kozo Morimoto; Atsuyuki Kurashima; Seigo Kitada; Sohkichi Matsumoto; et al. (Journal of Immunology Research)
Although tuberculosis remains a major global health problem, Bacille Calmette-Guérin (BCG) is the only available vaccine. However, BCG has limited applications, and a more effective vaccine is needed. Cellular mediated immunity (CMI) is thought to be the most important immune response for protection against Mycobacterium tuberculosis (Mtb). However, the recent failure of a clinical trial for a booster BCG vaccine and increasing evidence of antibody-mediated immunity prompted us to evaluate humoral immunity to Mtb-specific antigens. Using Enzyme-Linked ImmunoSpot and Enzyme-Linked ImmunoSorbent Assays, we observed less correlation of both CMI and IgG titers with patient clinical status, including serum concentration of C reactive protein. However, IgA titers against Mtb were significantly correlated with clinical status, suggesting that specific IgA antibodies protect against Mtb proliferation. In addition, in some cases, IgA antibody titers were significantly associated with the serum concentration of total albumin, which supports the idea that humoral immunity can be influenced by the nutritional status. Based on these observations, we propose that the induction of humoral immunity should be included as an option in TB vaccine development strategies.